2018
DOI: 10.1002/ece3.4596
|View full text |Cite
|
Sign up to set email alerts
|

Genomic divergence in allopatric Northern Cardinals of the North American warm deserts is linked to behavioral differentiation

Abstract: Biogeographic barriers are considered important in initiating speciation through geographic isolation, but they rarely indiscriminately and completely reduce gene flow across entire communities. Explicitly demonstrating which factors are associated with gene‐flow levels across barriers would help elucidate how speciation is initiated and isolation maintained. Here, we investigated the association of behavioral isolation on population differentiation in Northern Cardinals (Cardinalis cardinalis) distributed acr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 138 publications
0
13
0
Order By: Relevance
“…We found that there were no qualitative performance differences between the neural network with the 33 original summary statistics and the neural network with the 25 that resulted after the eight were removed (see Appendix S1 for classification information). We assumed a 3-year generation time for the snake species (after Ernst & Ernst, 2003) and a 1-year generation time for the bird species (after Provost et al, 2018).…”
Section: Ta B L E 1 Model Performancementioning
confidence: 99%
See 1 more Smart Citation
“…We found that there were no qualitative performance differences between the neural network with the 33 original summary statistics and the neural network with the 25 that resulted after the eight were removed (see Appendix S1 for classification information). We assumed a 3-year generation time for the snake species (after Ernst & Ernst, 2003) and a 1-year generation time for the bird species (after Provost et al, 2018).…”
Section: Ta B L E 1 Model Performancementioning
confidence: 99%
“…To evaluate the performance of our machine learning models on empirical data, we acquired previously published genetic data for four species of snake (Crotalus atrox, Crotalus scutulatus, Pituophis catenifer, and the Lampropeltis getula complex [between L. splendida/L. californiae];Myers et al, 2019) and one species of bird (Cardinalis cardinalis,Provost et al, 2018). All species had used reduced representation sequencing and had generated hundreds to thousands of individual loci, which we analyzed individually for all five taxa.…”
mentioning
confidence: 99%
“…Other parameter estimates are shown in the figure. Figure based on Provost, Mauck, Smith (2018) [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Resultsmentioning
confidence: 99%
“…The population started to decline again after the beginning of the Last Glacial Period (LGP). The decrease in effective population size observed at the beginning of Pleistocene might be due to the divergence of C. cardinalis into different subspecies ( Provost et al 2018 ). The population decline after the start of the LGP is consistent with the ecological niche model that indicates a dramatic range reduction for C. cardinalis during the LGP ( Smith et al 2011 ).…”
Section: Resultsmentioning
confidence: 99%